Korea's Growth Prospects : Overcoming Demographics and COVID-19 - Swiston, Andrew (Washington, D.C. : International Monetary Fund, 2021)
Korea's economy has leaped to high-income status thanks to several decades of sustained high growth. However, population aging and shifts in global demand provide headwinds for future growth and Korea now faces the effects of COVID-19 on economic activity. This paper asseses the expected drag on potential growth from these factors and discusses policies that could provide offsetting upward momentum by facilitating structural transformation. We find that potential output growth slowed to about 2 1\2 percent before the COVID-19 pandemic and would have fallen to 2 percent by 2030, mainly due to demographic factors. Moreover, there is a possibility of scarring from the COVID-19 shock as adjustment frictions from structural rigidities interact with shifts in demand and supply patterns, lowering investment and labor force participation. At the same time, industry-level analysis suggests ample scope to raise productivity, especially in services where productivity gains have lagged. Addressing these rigidities could offset a large proportion of the expected downward pressure on potential output.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Capacity; Capital; Employment; Intangible Capital; Investment